The amazing life of Ormond McGill : a new type of magic and hypnotism book in which a thoughtful professional reveals secrets of a lifetime /: a new type of magic and hypnotism book in which a thoughtful professional reveals secrets of a lifetime. (©2005) - Unknown
No abstract available